2019
DOI: 10.1021/acs.analchem.9b00658
|View full text |Cite
|
Sign up to set email alerts
|

First Community-Wide, Comparative Cross-Linking Mass Spectrometry Study

Abstract: The number of publications in the field of chemical cross-linking combined with mass spectrometry (XL-MS) to derive constraints for protein three-dimensional structure modeling and to probe protein–protein interactions has increased during the last years. As the technique is now becoming routine for in vitro and in vivo applications in proteomics and structural biology there is a pressing need to define protocols as well as data analysis and reporting formats. Such consensus formats should become accepted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
112
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 117 publications
(135 citation statements)
references
References 28 publications
13
112
0
Order By: Relevance
“…Currently, the most urgent task in the XL-MS community is to harmonize protocols and data reporting formats to ensure obtaining reproducible and reliable results. A recently conducted, community-wide XL-MS harmonization study revealed a great variety in the protocols employed as well as in the outcome, i.e., the number of identified cross-links, between the 32 participating groups [11]. This underlines the need for establishing generally accepted XL-MS protocols as well as common formats for data analysis and reporting results.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the most urgent task in the XL-MS community is to harmonize protocols and data reporting formats to ensure obtaining reproducible and reliable results. A recently conducted, community-wide XL-MS harmonization study revealed a great variety in the protocols employed as well as in the outcome, i.e., the number of identified cross-links, between the 32 participating groups [11]. This underlines the need for establishing generally accepted XL-MS protocols as well as common formats for data analysis and reporting results.…”
Section: Discussionmentioning
confidence: 99%
“…protein sequences and post-translational modifications) are typically not apparent with a technique like cryo-EM but are readily accessible by structural proteomics (3). At the same time, spatial information within and between proteins can be obtained by the use of cross-linking mass spectrometry (XL-MS) (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…The impact of cross-linker polarity on the final outcome was investigated on a well characterized BSA that was widely used as model protein for several cross-linking studies 20 . In this study, BSA was modified by equimolar mixtures of DSG ("light form") with d6-BS2G ("heavy form") and BS2G ("light form") with d6-DSG ("heavy form").…”
Section: Chemical Cross-linkingmentioning
confidence: 99%